2014
DOI: 10.2310/8000.2013.131261
|View full text |Cite
|
Sign up to set email alerts
|

Reported practice variation in pediatric pain management: a survey of Canadian pediatric emergency physicians

Abstract: Objectives: To describe pediatric emergency medicine (PEM) physicians' reported pain management practices across Canada and explore factors that facilitate or hinder pain management. Methods: This study was a prospective survey of Canadian pediatric emergency physicians. The Pediatric Emergency Research Canada physician database was used to identify participants, and a modified Dillman's Total Design Survey Method was used for recruitment.Results: The survey response rate was 68% (139 of 206). Most physicians … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
49
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(52 citation statements)
references
References 39 publications
(64 reference statements)
1
49
0
2
Order By: Relevance
“…Our results support the possibility that awareness has increased regarding the importance of providing analgesia to children with acute abdominal pain. Our findings are also consistent with a 2013 Canadian survey of PEPs 24 that found only 4% of respondents stated they would withhold analgesia in the case of a child with suspected "surgical abdomen." However, both the 2013 self-reported finding and our findings may be incongruent with directly observed practice.…”
Section: Discussionsupporting
confidence: 81%
“…Our results support the possibility that awareness has increased regarding the importance of providing analgesia to children with acute abdominal pain. Our findings are also consistent with a 2013 Canadian survey of PEPs 24 that found only 4% of respondents stated they would withhold analgesia in the case of a child with suspected "surgical abdomen." However, both the 2013 self-reported finding and our findings may be incongruent with directly observed practice.…”
Section: Discussionsupporting
confidence: 81%
“…2 In spite of this, oligoanalgesia and inadequate pain management constitute a phenomenon that is still a major problem in clinical practice, 5,10,11 as previously seen and demonstrated in our setting. The main problems that have been detected are the scarce assessment of pain, the use of treatments as needed instead of at scheduled intervals, and the administration of analgesics in the emergency room to less than a half of patients.…”
Section: Discussionmentioning
confidence: 85%
“…1 A l t h o u g h p a i n i s a c o m m o n symptom seen at the emergency department, 2 several studies have demonstrated that pain management is inadequate. 3 There are multiple causes for this: difficulty to assess pain, fear to use strong analgesics, and use of medications on an as needed basis instead of at scheduled intervals.…”
Section: Introductionmentioning
confidence: 99%
“…2 A pesar de esto, la oligoanalgesia y el inadecuado tratamiento del dolor es un fenómeno que continúa constituyendo un problema importante en la práctica clínica, 5,10,11 como se ha visto previamente y se ha demostrado en nuestro medio. Los principales problemas detectados han sido escasa evaluación del dolor, uso de tratamientos a demanda en lugar de pautado y administración de analgésicos en el SUP en menos de la mitad de los pacientes.…”
Section: Discussionunclassified
“…1 A pesar de que el dolor es un síntoma frecuente en los servicios de urgencias, 2 numerosos estudios han demostrado que su manejo es inadecuado. 3 Existen múltiples causas: dificultad para su evaluación, miedo al uso de analgésicos potentes y uso de medicación a demanda en lugar de pautada.…”
Section: Introductionunclassified